Perlindungan Hukum Anak dibawah Umur terhadap Pengaruh Narkoba di Kelurahan Sei Mati - Nurul Tahlida Lubis; Muhammad Ridwan Lubis (Pemuliaan Keadilan, 2026)
This study aims to analyze the legal protection of minors affected by drug abuse in Sei Mati Village, Medan Maimun District. The problems examined in this study include the legal regulations concerning children involved in drug abuse, the implementation of legal protection, and the inhibiting factors in its application. This research employs an empirical legal research method with a qualitative approach, which examines law based on real conditions in society (law in action). Data collection techniques were carried out through interviews, observations, and documentation involving informants consisting of children who had been involved in drug abuse, parents, and community leaders. The results of the study indicate that the legal regulation concerning children involved in drug abuse has been stipulated in Law Number 35 of 2009 concerning Narcotics, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, and Law Number 35 of 2014 concerning Child Protection, which emphasize rehabilitation and guidance approaches. The implementation of legal protection in Sei Mati Village tends to prioritize a familial approach, guidance, and social supervision rather than punishment. However, the implementation of legal protection still faces several obstacles, such as low legal awareness among the community, weak parental supervision, negative peer influence, and limited rehabilitation facilities and professional assistance. Therefore, synergy among the government, law enforcement officials, families, and the community is needed to enhance the effectiveness of legal protection for children, particularly in preventing and addressing drug abuse.